2011
DOI: 10.1002/btpr.644
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the manufacturability of Escherichia coli high cell density fermentations

Abstract: The physical and biological conditions of the host cell obtained at the end of fermentation influences subsequent downstream processing unit operations. The ability to monitor these characteristics is central to the improvement of biopharmaceutical manufacture. In this study, we have used a combination of techniques such as adaptive focus acoustics (AFA) and ultra scale-down (USD) centrifugation that utilize milliliter quantities of sample to obtain an insight into the interaction between cells from the upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Since E. coli does not naturally secrete recombinant proteins, this is due to release of periplasmic Fab by outer membrane damage. This is problematic for industrial processes since periplasmic release requires bacteria to be physically intact to permit selective release of periplasmically‐targeted recombinant proteins and prevent release of cytoplasmic proteins during centrifugal cell harvesting or osmotic release procedures . If bacteria are physically weakened, for example by RPP‐induced stress, then far more protein is released, complicating DSP; the advantages of periplasmic targeting and release are minimal compared with cytoplasmic expression, lysis and purification from whole cell lysate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since E. coli does not naturally secrete recombinant proteins, this is due to release of periplasmic Fab by outer membrane damage. This is problematic for industrial processes since periplasmic release requires bacteria to be physically intact to permit selective release of periplasmically‐targeted recombinant proteins and prevent release of cytoplasmic proteins during centrifugal cell harvesting or osmotic release procedures . If bacteria are physically weakened, for example by RPP‐induced stress, then far more protein is released, complicating DSP; the advantages of periplasmic targeting and release are minimal compared with cytoplasmic expression, lysis and purification from whole cell lysate.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that stress minimization by decreasing culture temperature and inducer concentration can be used to improve not only recombinant protein yields and folding but also correct subcellular targeting and overall cell integrity for subsequent cell harvest and protein release steps . Careful balancing of increases in inducer concentration and decreases in growth and induction temperature allowed optimization of Fab D1.3 yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During fermentation, as the limit of the periplasm is reached, cells begin to lose viability and leak the Fab' product and other intracellular content to the fermentation broth. Apart from product loss in late stage fermentation, the remaining viable cells become more fragile and break fourfold more than those harvested at an earlier stage, if subjected to the equivalent shear level of that in an industrial centrifuge . As cell lysis occurs in late stage fermentation, leakage of product to the fermentation broth also acts to increase the broth viscosity, as large quantities of chromosomal DNA and other intracellular content are released simultaneously into the broth .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the critical concentration required for effective downstream processing can increase as a function of time in response to the accumulation of contaminants, e.g. arising from cell lysis, in the fermentation broth . The right boundary, determined by the inherent biocatalyst stability, can be tilted inwards, if, for instance, subtoxic product concentrations are accompanied by increased microbial energy demands compromising the efficiency of metabolic network operation .…”
Section: Implications For Bioprocess Development and Conclusionmentioning
confidence: 99%